SOCIAL DELIVERY OF IMMIGRATION POLYTECHNIC CADETS WITH COMMUNITY IN THE MIDDLE OF THE COVID-19 PANDEMIC - Trestiati Lutfiyah Khanza; Mochammad Ryanindityo (Polteknik Imigrasi, 2021)
The figure of a Cadet who has a knight spirit and his considered have high integrity. We have a deep sense of empathy and sympathy for the environment, so that it can be well known by the wider community.On this occasion in the midst pandemic covid-19 , Cadets from Immigration Polytechnic took the initiative to distribute aid funds that could be useful for the people living in the local area and we hope can help each other.At this time all immigrationpolytechnic cadets who are currently still carrying out distances lectures it hopes that they will continue to carry out useful activities and always reflect their cadet attitude.